2020
DOI: 10.1186/s41235-020-00211-y
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening spatial reasoning: elucidating the attentional and neural mechanisms associated with mental rotation skill development

Abstract: Spatial reasoning is a critical skill in many everyday tasks and in science, technology, engineering, and mathematics disciplines. The current study examined how training on mental rotation (a spatial reasoning task) impacts the completeness of an encoded representation and the ability to rotate the representation. We used a multisession, multimethod design with an active control group to determine how mental rotation ability impacts performance for a trained stimulus category and an untrained stimulus categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
(90 reference statements)
3
14
0
1
Order By: Relevance
“…Consistent with previous findings our study revealed that aspects of the superior parietal lobe were more active during both down-and up-regulation compared to their respective viewing conditions. This observation is consistent with the role of superior aspects of the parietal lobe being involved in aspects of visual mental imagery (Dijkstra et al, 2017; Moen et al, 2020) and emotion regulation via reappraisal and distraction (Kanske et al, 2011; McRae et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with previous findings our study revealed that aspects of the superior parietal lobe were more active during both down-and up-regulation compared to their respective viewing conditions. This observation is consistent with the role of superior aspects of the parietal lobe being involved in aspects of visual mental imagery (Dijkstra et al, 2017; Moen et al, 2020) and emotion regulation via reappraisal and distraction (Kanske et al, 2011; McRae et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Spatial reasoning is one of the most important human skills, useful for many daily activities [1]. It involves the mental representations of the shape of objects, their locations, as well as cognitive processes of transformation of objects and movement through space [2].…”
Section: Introductionmentioning
confidence: 99%
“…It involves the mental representations of the shape of objects, their locations, as well as cognitive processes of transformation of objects and movement through space [2]. We think spatially as: (a) behind the wheel, we try to quickly compare the incoming visuospatial information flow with our mental representation of the map we saw earlier, as well as: (b) when preparing a trip, we try to find the best way to arrange luggage in the vehicle's trunk [1,2]. Often, people seem to be able to encode visuospatial information and adopt it into decisions and complex motor actions that allow them to control high-speed locomotion [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations